2008
DOI: 10.1901/jeab.2008.89-31
|View full text |Cite
|
Sign up to set email alerts
|

Induced Attack During Fixed‐ratio and Matched‐time Schedules of Food Presentation

Abstract: Adjunctive or induced behavior is generated during a variety of schedules of reinforcement. Several theoretical conceptualizations suggest that rate of reinforcement is the primary variable controlling the strength or levels of induced behavior. The operant response requirement within the schedule context has not been extensively studied as a determinant of induced responding. In the present study, levels of induced attack by food-deprived pigeons against restrained conspecifics were compared during response-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…It is distinguished from operant and rule governed behavior-which involves incremental shaping or verbal learning, respectively (cf., Killeen & Pellón, 2013). Previously viewed as insufficiently understood to have explanatory value (Segal, 1972), schedule-induced behavior is now implicated as potentially causal with respect to complex biobehavioral phenomena including foraging and fat storage (Anselme & Güntürkün, 2019), addictive behavior (Berridge & Robinson, 2016), creativity (Pryor, Haag, & O'Reilly, 1969), superstition (Skinner, 1948;cf., Staddon & Simmelhag, 1971), aggression (Kupfer, Allen, & Malagodi, 2008), and compulsive and religious behavior (Strand, 2009).…”
mentioning
confidence: 99%
“…It is distinguished from operant and rule governed behavior-which involves incremental shaping or verbal learning, respectively (cf., Killeen & Pellón, 2013). Previously viewed as insufficiently understood to have explanatory value (Segal, 1972), schedule-induced behavior is now implicated as potentially causal with respect to complex biobehavioral phenomena including foraging and fat storage (Anselme & Güntürkün, 2019), addictive behavior (Berridge & Robinson, 2016), creativity (Pryor, Haag, & O'Reilly, 1969), superstition (Skinner, 1948;cf., Staddon & Simmelhag, 1971), aggression (Kupfer, Allen, & Malagodi, 2008), and compulsive and religious behavior (Strand, 2009).…”
mentioning
confidence: 99%
“…Results of several experiments suggest that, contrary to Sidman's assumptions, positive reinforcement contingencies may exhibit aversive functions. This can be seen, for example, in experiments on aggression induced by positive reinforcement (Kupfer et al, 2003;Richards & Rilling 1972), self-imposed time-out of positive reinforcement (Azrin, 1961;Lydersen, 1997), as well as in the relativity of the reinforcing or aversive function of a given schedule of reinforcement depending on the available alternatives (Everly et al, 2014;Retzlaff et al, 2017).…”
Section: Problems With Sidman's Approach To Coercionmentioning
confidence: 99%
“…Research by Staddon and Simmelhag (1971) and others has confirmed that the behavior of nonhuman animals (Anderson & Shettleworth, 1977;Flagel, Watson, Akil, & Robinson, 2008;Flagel, Watson, Robinson, & Akil, 2007;Innis, Simmelhag-Grant, & Staddon, 1983;Kupfer, Allen, & Malagodi, 2008) and humans (Muller, Crow, & Cheney, 1979;Porter, Brown, & Goldsmith, 1982;Prior, Wallace, & Milton, 1984) exposed to response-independent reinforcement schedules is sometimes odd in that it is inconsistent with obtaining the anticipated reinforcer. However, the patterning of the behavior is more complex than Skinner reported.…”
Section: Schedule-based Variabilitymentioning
confidence: 99%